Temporary Balloon Occlusion of the Common Hepatic Artery for Yttrium-90 Glass Microspheres Administration in a Patient with Hepatocellular Cancer and Renal Insufficiency - Justin Smith; Ravi Murthy; Amit Lahoti; Bruno Odisio; Rony Avritscher; Beth Chasen; Armeen Mahvash (Case Reports in Radiology)
The most severe complication of yttrium-90 therapy is gastrointestinal ulceration caused by extrahepatic dispersion of microspheres. Standard pretreatment planning requires extensive angiographic evaluation of the hepatic circulation and embolization of hepatoenteric collaterals; however, in patients with severe renal insufficiency, this evaluation may lead to acute renal failure. In order to minimize iodinated contrast utilization in a patient with preexisting severe renal insufficiency, the authors describe the use of a balloon catheter for temporary occlusion of the common hepatic artery to induce transient redirection of flow of the hepatoenteric arteries towards the liver, in lieu of conventional coil embolization.